Adult diphteria: possible transmission of Corynebacterium diphtheriae from unvaccinated child? - Kandasamy, Thenmalar; Muhamad Damanhuri, Fatimahtuz Zahrah; Zaini, Adillahtul Bushro; Zakariah, Siti Zulaikha; Ibrahim, Rosni (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
A case of a toxigenic strain of Corynebacterium diphtheriae in an immunocompetent adult is presented, with the possibility of the adult acquiring the infection from her unvaccinated child. The abovementioned adult is a 29-year-old housewife who was previously immunised with diphtheria, tetanus, and pertussis (DTaP) vaccination in childhood, who presented fever, cough, sore throat, hoarseness of voice, odynophagia, and bilaterally enlarged tonsils. A throat swab confirmed the presence of toxigenic Corynebacterium diphtheriae. The patient was given 80,000 international units (IU) dose of diphtheria antitoxin (DAT) and treated with 2.4 million units (MU) QID intravenous penicillin and oral erythromycin 800 mg twice daily for two weeks. The patient responded well to the treatment and recovered with no cardiovascular or neurotoxicity.